Implementasi Program Greeting melalui Model The 4 Disciplines of Execution (4DX) di Rumah Sakit Umum Abdhi Famili, Indonesia: Penelitian - Arlan Kurnia, Jodii (Cermin Dunia Kedokteran, 2026)
Introduction: One important factor influencing patient satisfaction is the culture of staff friendliness, so an effective execution strategy is necessary to drive service transformation in hospitals. This study aims to evaluate the implementation of the Greeting Program using the 4 Disciplines of Execution (4DX) model at RSU Abdhi Famili and its impact on patient satisfaction. Methods: A mixed-methods approach with a sequential exploratory design, integrating both qualitative and quantitative perspectives. In the qualitative phase, the transformation process toward a culture of hospitality was described through four key disciplines: establishing Wildly Important Goals (WIGs), executing lead measures, displaying performance scoreboards, and maintaining a rhythm of accountability. The quantitative phase studied the relationship between the implementation of the Greeting Program and patient satisfaction with a cross-sectional design, using a questionnaire instrument on 80 inpatients, and analyzed using the Chi-square test. Results: In the qualitative phase, all four disciplines were executed, with final achievement rates in the medical service area: the Polyclinics, Inpatients, and Emergency Department Units each reached 100%, and the Perinatology and Maternity Units each achieved 80%. Medical Support area, Nutrition, and Radiology Units reached 100%, whereas the Admission, Laboratory, and Pharmacy Units attained 89%, 88%, and 75%, respectively. In the quantitative phase, Chi-square analysis indicateda significant association between the implementation of the Greeting Program and patient satisfaction levels (p < 0.05). Conclusion: These findings confirm that the execution strategy implemented through the 4DX model effectively improves service quality and has a positiveimpact on patient satisfaction with health services at RSU Abdhi Famili.